Achieving Fair and Equal Access to Vaccination for Persons with Disabilities in Indonesia: A Lesson Learned from the Vaccination Programme in the COVID-19 Outbreak - Kusumawati, Erna Dyah; Firdausy, Adriana Grahani; Sasmini, Sasmini (University of Jember, 2024)
The World Health Organisation has recommended that its member states conduct national vaccination programs based on fair and equal access principles. COVID-19 has had more severe impacts on persons with disabilities (PwDs). This article focuses on how the provisions of international human rights instruments obligate countries to provide vaccination for PwDs. Further, these provisions will be used to analyse the law and policy adopted by the Indonesian government related to the vaccination program designed for this group. This article used both normative/doctrinal and empirical legal research methods. Based on international human rights law, access to vaccines and medical technology are elements of the right to health under the AAAQ principles. Member states should consider groups’ vulnerabilities, risks, and needs when designing the vaccination program. Some groups risk experiencing a more significant burden from the pandemic due to underlying social, geographic, or biomedical factors. PwDs are people coming from diverse backgrounds. Thus, the challenges they face will vary according to age diversity, gender, types of disability, ethnicity, sexual orientation, and migration status. The results show that Indonesia, during the first vaccine rollout, did not explicitly mention disability as a priority. PwDs have experienced barriers in accessing vaccination due to a few persistent problems. In the future, national vaccination programs should include measures to overcome such barriers and ensure that PwDs have equal access to the vaccine and other healthcare services. Such access will enable the fulfilment of the right to health of the PwDs as guaranteed both under international human rights law and domestic law. In addition, future healthcare policy should put PwDs at the centre and address the unique needs and preferences of disabled people, including their cultural and language requirements. Keywords: COVID-19 Vaccine, Persons with Disability, Equal Access, Indonesia